2018
DOI: 10.1111/pce.13362
|View full text |Cite
|
Sign up to set email alerts
|

CAX1 suppresses Cd‐induced generation of reactive oxygen species in Arabidopsis halleri

Abstract: The molecular analysis of metal hyperaccumulation in species such as Arabidopsis halleri offers the chance to gain insights into metal homeostasis and into the evolution of adaptation to extreme habitats. A prerequisite of metal hyperaccumulation is metal hypertolerance. Genetic analysis of a backcross population derived from Arabidopsis lyrata × A. halleri crosses revealed three quantitative trait loci for Cd hypertolerance. A candidate gene for Cdtol2 is AhCAX1, encoding a vacuolar Ca /H antiporter. We devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 81 publications
(159 reference statements)
1
25
0
Order By: Relevance
“…Overexpression of the AhZIP6 copies in A. thaliana or their extinction in A. halleri altered cadmium tolerance but had no impact on zinc tolerance or the ionome of the plants, Text S1. A. thaliana transformation was performed by floral dip (Clough & Bent, 1998) and Agrobacterium tumefaciens (GV3101, pMP90) mediated stable transformation of A. halleri was performed using a tissue-culture based procedure (Ahmadi et al, 2018;Hanikenne et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the AhZIP6 copies in A. thaliana or their extinction in A. halleri altered cadmium tolerance but had no impact on zinc tolerance or the ionome of the plants, Text S1. A. thaliana transformation was performed by floral dip (Clough & Bent, 1998) and Agrobacterium tumefaciens (GV3101, pMP90) mediated stable transformation of A. halleri was performed using a tissue-culture based procedure (Ahmadi et al, 2018;Hanikenne et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in plants occurs as a consequence of many abiotic stresses including extreme temperatures, drought, salinity, osmotic stress, and pollutants (e.g., heavy metals or herbicides) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…halleri with its nonhyperaccumulating relative A rabidopsis lyrata ssp. petraea , quantitative trait loci (QTLs) for Zn accumulation (Willems et al, ), Zn tolerance (Willems et al, ), Cd accumulation, and Cd tolerance (Ahmadi, Corso, Weber, Verbruggen, & Clemens, ; Courbot et al, ) were detected. Second, comparative transcriptome studies with A .…”
Section: Introductionmentioning
confidence: 99%
“…First, in backcross populations derived from interspecific crosses of A. halleri with its nonhyperaccumulating relative Arabidopsis lyrata ssp. petraea, quantitative trait loci (QTLs) for Zn accumulation (Willems et al, 2010), Zn tolerance , Cd accumulation, and Cd tolerance (Ahmadi, Corso, Weber, Verbruggen, & Clemens, 2018;Courbot et al, 2007) were detected. Second, comparative transcriptome studies with A. halleri genotypes and Arabidopsis thaliana revealed that the transcripts of numerous metal homeostasis genes are constitutively more abundant in A. halleri (Becher, Talke, Krall, & Krämer, 2004;Talke, Hanikenne, & Krämer, 2006;Weber, Harada, Vess, von Roepenack-Lahaye, & Clemens, 2004).…”
mentioning
confidence: 99%